Knowledge and Willingness to Act Pro-Environmentally: Perspectives from IEA TIMSS 2019 and ICCS 2016 Data - Isac, Maria Magdalena; Sandoval-Hernández, Andrés; Sass, Wanda (IEA Research for Education, 2025)
This open access book utilizes data from two large-scale international assessments—TIMSS 2019 and ICCS 2016—to investigate the extent to which education for sustainable development outcomes is conveyed and accomplished within various educational systems. Specifically, it aims to expand the understanding of how students' environmental knowledge levels and their willingness to act in a pro-environmentally manner can differ across and within countries. The book also examines whether certain opportunities to learn about environmental issues in secondary schools show promise in enhancing young people's environmental knowledge and attitudes.